Impact of Pharmacists' Interventions and Simvastatin Dose Restrictions. (January 2014) - Shoulders, Bethany R.; Franks, Andrea S.; Barlow, Patrick B.; Williams, Juli D.; Farland, Michelle Z.
Background: On June 8, 2011, the United States Food and Drug Administration (FDA) reported safety concerns regarding statin-related myopathies and advised further restrictions on simvastatin dosing. These restrictions reduced the maximum dose for specific patient characteristics, primarily certain concomitant medications.Objective: The purpose of this study was to compare the effectiveness of 2 different pharmacist-conducted educational interventions on appropriate simvastatin use in the primary care setting.Methods: This retrospective cohort analysis was conducted in 2 academic medical center clinics. Patients prescribed simvastatin before June 8, 2011, requiring dosage adjustment based on labeling changes were evaluated for study inclusion. The pharmacists' interventions included: 30-minute didactic session for prescribers or patient-specific recommendation communicated with the physician during the patient's follow-up visit. Primary outcomes were the number of patients prescribed FDA-recommended simvastatin doses after pharmacist intervention and the intervention's impact on low-density lipoprotein (LDL).Results: Medical record review identified 1173 patients prescribed simvastatin prior to June 8, 2011; 126 patients qualified for study inclusion. After controlling for baseline characteristics, the likelihood of patients being prescribed an appropriate dose postintervention increased if they were in the patient-specific recommendation group (odds ratio [OR] = 10.59; 95% CI = 3.43-32.69; P < .0001). LDL change occurred at a similar rate between intervention groups ( P = .652).Conclusion: Following FDA labeling changes for simvastatin, patient-specific recommendations made by pharmacists correlated with a greater likelihood of appropriate simvastatin dosing compared with a one-time didactic education session. Patient-specific recommendations positively affect prescribing habits and making steps to improve patient safety.